Developing agent-based simulation models for social systems engineering studies: a novel framework and its application to modelling peacebuilding activities - Siebers, Peer-Olaf; Figueredo, Grazziela P.; Hirono, Miwa; Skatova, Anya (Wiley, 2017)
When looking for a "what-if" analysis tool to support social systems engineering studies, agent-based modelling and simulation should be the method of choice. It is a well-established method for studying human-centric systems. Developing such models, however, is not an easy task, and there is not much guidance around, that clearly explains how this is done. In this book chapter we present a novel framework to guide teams through the process of model development from conceptual design to implementation. While we describe the tools that can be used for this purpose we also provide guidance on how the required information can be produced. We borrow ideas from software engineering to define a more structured approach to problem analysis and model design. We use an illustrative example (international peacebuilding activities in South Sudan) to demonstrate how the novel framework has been applied in a real world setting. This illustrative example confirms that a structured approach is very helpful when dealing with a multidisciplinary team and a case-based project.